Modulation of the mTOR pathway plays a central role in dendritic cell functions after Echinococcus granulosus antigen recognition - Rodríguez Rodrígues, Christian Fernando Ariel (2020)
Immune evasion is a hallmark of persistent echinococcal infection, comprising modulation of innate immune cells and antigen-specific T cell responses. However, recognition of Echinococcus granulosus by dendritic cells (DCs) is a key determinant of the host?s response to this parasite. Given that mTOR signaling pathway has been described as a regulator linking metabolism and immune function in DCs, we reported for the first time in these cells, global translation levels, antigen uptake, phenotype, cytokine transcriptional levels, and splenocyte priming activity upon recognition of the hydatid fluid (HF) and the highly glycosylated laminar layer (LL). We found that LL induced a slight up-regulation of CD86 and MHC II in DCs and also stimulated the production of IL-6 and TNF-α. By contrast, HF did not increase the expression of any co-stimulatory molecules, but also down-modulated CD40 and stimulated the expression of the anti-inflammatory cytokine IL-10. Both parasitic antigens promoted protein synthesis through mTOR activation. The use of rapamycin decreased the expression of the cytokines tested, empowered the down-modulation of CD40 and also reduced splenocyte proliferation. Finally, we showed that E. granulosus antigens increase the amounts of LC3-positive structures in DCs which play critical roles in the presentation of these antigens to T cells.